Financial behavior and problems among college students in Malaysia: research and education implication - Sabri, Mohamad Fazli; Othman, Mohd Amin; Masud, Jariah; Paim, Laily; MacDonald, Maurice; K. Hira, Tahira (2008)
For a majority of students, university attendance is the first time they have experienced financial independence without a parent's supervision. With the expansion of educational services in Malaysia, university or college students have become one of the important consumer market segments, for two reasons. First, this group has expanded purchasing power, with easily available educational loans. Second, this student segment of the population has better potential earnings than any other segment of the population. There has been limited study on financial behavior and problems among Malaysians, especially college students, since the concern over the role of young consumers is relatively new.